Hubungan Jarak Kehamilan, Pekerjaan dan Paritas dengan Kejadian Hiperemesis Gravidarum Pada Ibu Hamil - Nurhasanah Nurhasanah; Siti Aisyah; Rizki Amalia (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Nausea and vomiting are common in early pregnancy. Nausea and vomiting usually occur in the morning, because it is also called morning sickness, but it is also possible to occur during the day and at night. About 50-60 percent of pregnancies are accompanied by nausea and vomiting, of as many as 360 pregnant women 2% of them experience nausea and vomiting in the morning and 80% experience nausea and vomiting throughout the day. This study aims to determine the relationship between pregnancy distance, occupation and parity with the incidence of hyperemesis gravidarum in pregnant women at Amanna Baturaja RSIA 2020. The design of this study was an analytical survey using a cross sectional study design. The population in this study were all TM 1 pregnant women who had their pregnancy checked at RSIA Amanna Baturaja Kec. East Baturaja in 2020, totaling 232 respondents and a total sample of 70 respondents. The sampling technique used is systematic random sampling. Data analysis used Chi Square statistical test with Pvalue value (0.05). The results of this study based on the Chi Square test, the pregnancy distance Pvalue = 0.000, work Pvalue = 0.02 and parity Pvalue = 0.03. Midwives are expected to improve the quality of health services for pregnant women to prevent hyperemesis gravidarum.